Differential impact of plant-based selenium nanoparticles on physio-biochemical properties, antioxidant defense system and protein regulation in fruits of huanglongbing-infected ‘Kinnow’ mandarin plants - Ikram, Muhammad; Raja, Naveed Iqbal; Mohamed, Azza H.; Mashwani, Zia-Ur-Rehman; Omar, Ahmad A.; Gharibi, Hassan; Zubarev, Roman A. (Frontiers in Plant Science, 2024)
Huanglongbing disease (HLB) is the most severe citrus disease destroying Citrus reticulata L. ‘Kinnow’, the most commonly grown mandarin in Pakistan. It is caused by Candidatus Liberibacter bacterial species and it spreads through the sucking Asian citrus psyllid insect. The current study was designed to investigate the potential impact of plant extract mediated selenium nanoparticles (SeNPs) on antioxidant defense system, fruit quality and protein regulation in the fruits of HLB-infected ‘Kinnow’ mandarin plants. Garlic cloves extract was used as reducing and capping agent for the synthesis of SeNPs. Various concentrations of SeNPs (25, 50, 75, and 100 mg L−1) were exogeneously applied to HLB-positive citrus plants. SeNPs at the concentration of 75 mg L-1 affected positively fruit physio-biochemical parameters, e.g., peel thickness, peel weight, fruit weight, fruit diameter, total soluble solids, juice volume, ascorbic acid content and reduced total acidity. Furthermore, SeNPs also enhanced the amounts of total protein and total sugar as well as elevated antioxidant enzymes, e.g., superoxide dismutase, peroxidases, and catalases. Non-enzymatic antioxidant content, e.g., total phenolic and total flavonoids, was also elevated. Proteomics analysis revealed that exposure to SeNPs at the concentration of 75 mg·L–1 significantly altered in HLB infected mandarin fruting plants the expression of proteins associated with transcription, protection, cell wall biogenesis, cell wall organization, reproduction, stamen formation, embryo development, inflorescence development, as well as translation and response to oxidative stress. Our results revealed that foliar application of SeNPs influences the protein contents positively, therefore ameliorating fruit physio-biochemical quality by boosting antioxidant defense systems of HLB-infected ‘Kinnow’ mandarin plants.